The Visioning of Policy and the Hope of Implementation: Support for Graduate Students’ Teaching at a Canadian Institution - Hoessler, Carolyn; Godden, Lorraine (Canadian Journal of Higher Education, 2015)
Graduate students teach within the complex higher education environment of financial constraint, greater student diversity, and growing graduate enrolment (e.g., Austin, 2003). Teaching roles offer financial support and skill development while multiplying responsibilities (Price, 2008). Across the national working papers and institutional reports, policies, and websites that we analyzed, support for graduate students was linked to their roles (e.g., teaching assistants). Formal messages about responsibility varied; national documents pointed to institutions, while institutional documents pointed to departments, courses, and individual graduate students. Most supports for graduate students reported were already existing piecemeal supports with limited implementation, despite policy recommendations for broad, flexible, open-ended, and recognized programming. Future research is needed to further clarify the pathways from vision to action.